Bright insights into palladium-triggered local chemotherapy. Issue 37 (25th July 2018) - Bray, Thomas L.; Salji, Mark; Brombin, Alessandro; Pérez-López, Ana M.; Rubio-Ruiz, Belén; Galbraith, Laura C. A.; Patton, E. Elizabeth; Leung, Hing Y.; Unciti-Broceta, Asier
Abstract : We report fundamental insights into the validity, reliability and clinical feasibility of using heterogeneous Pd catalysts as implantable devices to accurately activate chemotherapy within a tumour. Abstract : The incorporation of transition metal catalysts to the bioorthogonal toolbox has opened the possibility of producing supra-stoichiometric amounts of xenobiotics in living systems in a non-enzymatic fashion. For medical use, such metals could be embedded in implantable devices ( i.e. heterogeneous catalyst) to "synthesize" drugs in desired locations ( e.g. in a tumour) with high specificity and for extended periods of time, overcoming the useful life limitations of current local therapy modalities directed to specific organ sites ( e.g. brachytherapy, controlled release systems). To translate this approach into a bona fide therapeutic option, it is essential to develop clinically-accessible implantation procedures and to understand and validate the activation process in relevant preclinical models. Herein we report the development of a novel Pd-activatable precursor of the red-fluorescent drug doxorubicin and Pd devices of optimized size and activity. Screening in state-of-the-art cancer models provided fundamental insights into the insertion protocols, safety and stability of the devices and into the prodrug distribution profile before and after activation.